Epstein–Barr virus-specific CD8+ T lymphocytes from diffuse large B cell lymphoma patients are functionally impaired. (11th September 2015) - Cárdenas, D; Vélez, G; Orfao, A; Herrera, M V; Solano, J; Olaya, M; Uribe, A M; Saavedra, C; Duarte, M; Rodríguez, M; López, M; Fiorentino, S; et al.
Summary: Epstein–Barr virus (EBV) is a persistent virus with oncogenic capacity that has been implicated in the development of aggressive B cell lymphomas, primarily in immunosuppressed individuals, although it can be present in immunocompetent individuals. Changes in the function and clonal diversity of T lymphocytes might be implied by viral persistence and lymphoma development. The aim of the present study was to evaluate the frequency, phenotype, function and clonotypical distribution of EBV-specific T cells after peripheral blood stimulation with a virus lysate in newly diagnosed patients with diffuse large B cell lymphoma (DLBCL) aged more than 50 years without prior histories of clinical immunosuppression compared with healthy controls. Our results showed impaired EBV-specific immune responses among DLBCL patients that were associated primarily with decreased numbers of central and effector memory CD8 + T lymphocytes. In contrast to healthy controls, only a minority of the patients showed CD4 + /tumour necrosis factor (TNF)-α + T cells expressing T cell receptor (TCR)-Vβ17 and CD8 + /TNF-α + T cells with TCR-Vβ5·2, Vβ9 and Vβ18 in response to EBV. Notably, the production of TNF-α was undetectable among TCR-Vβ5·3 +, Vβ11 +, Vβ12 +, Vβ16 + and Vβ23 + CD8 + T cells. In addition, we observed decreased numbers of CD4 + /TNF-α + and CD8 + /TNF-α +, CD8 + /interleukin (IL)-2 + and CD8 + /TNF-α + /IL-2 + T lymphocytes in the absence of T cells capable of producing TNF-α, IL-2 and IFN-γ after EBV stimulation simultaneously. Moreover, DLBCL patients displayed higher IL-10 levels both under baseline conditions and after EBV stimulation. These findings were also observed in patients with positive EBV viral loads. Prospective studies including a large number of patients are needed to confirm these findings.